Patterns of Lynx Predation at the Interface between Protected Areas and Multi-Use Landscapes in Central Europe - Belotti, Elisa; Weder, Nicole; Bufka, Luděk; Kaldhusdal, Arne; Küchenhoff, Helmut; Seibold, Heidi; Woelfing, Benno; Heurich, Marco (PLoS One, 2015)
In Central Europe, protected areas are too small to ensure survival of populations of large carnivores. In the surrounding areas, these species are often persecuted due to competition with game hunters. Therefore, understanding how predation intensity varies spatio-temporally across areas with different levels of protection is fundamental. We investigated the predation patterns of Eurasian lynx (Lynx lynx) on roe deer (Capreolus capreolus) and red deer (Cervus elaphus) in both protected areas and multi-use landscapes of the Bohemian Forest Ecosystem. Based on 359 roe and red deer killed by 10 GPS-collared lynx, we calculated the species-specific annual kill rates and tested for effects of season and lynx age, sex and reproductive status. Because roe and red deer in the study area concentrate in unprotected lowlands during winter, we modeled spatial distribution of kills separately for summer and winter and calculated-the probability of a deer killed by lynx and-the expected number of kills for areas with different levels of protection. Significantly more roe deer (46.05-74.71/year/individual lynx) were killed than red deer (1.57-9.63/year/individual lynx), more deer were killed in winter than in summer, and lynx family groups had higher annual kill rates than adult male, single adult female and subadult female lynx. In winter the probability of a deer killed and the expected number of kills were higher outside the most protected part of the study area than inside; in summer, this probability did not differ between areas, and the expected number of kills was slightly larger inside than outside the most protected part of the study area. This indicates that the intensity of lynx predation in the unprotected part of the Bohemian Forest Ecosystem increases in winter, thus mitigation of conflicts in these areas should be included as a priority in the lynx conservation strategy.
Keywords: Forests; Europe; zvířata; roční období; Predatory Behavior; mužské pohlaví; Lynx; Evropa; Seasons; zachování přírodních zdrojů; ženské pohlaví; predátorské chování; Animals; Food Chain; Deer; lesy; potravní řetězec; vysoká zvěř; Male; Conservation of Natural Resources; Female